1980
DOI: 10.1099/00221287-116-1-1
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Rhizobium Genetics: The Fourth Fleming Lecture

Abstract: The rhizobia are Gram-negative bacteria of major agricultural importance because of their ability to form nitrogen-fixing nodules on the roots of leguminous plants. The nitrogen fixation genes are carried by the rhizobia and are possibly only expressed in nature within the root nodule. Usually a given strain of Rhizobium can nodulate only a limited number of legume species. For temperate species this has given rise to a taxonomic classification based on the range of host plants that are nodulated. For example,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1980
1980
1985
1985

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This chromosome mobilizati ilar in several respects to the chrc mobilization mediated by RP4 or R68. eral species of the Rhizobiaceae (2). ) teristic of R68.45-mediated conjugati( mobilization of large segments of ti chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…This chromosome mobilizati ilar in several respects to the chrc mobilization mediated by RP4 or R68. eral species of the Rhizobiaceae (2). ) teristic of R68.45-mediated conjugati( mobilization of large segments of ti chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Several books on N2 fixation have been published recently (32,67,90,101,154,178), and a variety of specialized topics concerning N2 fixation have been reviewed, including biochemistry (62,71,126,147,249), the Rhizobium infection process (16,27,53,190), nonlegume symbioses (1), cyanobacteria (95,250), and genetics and regulation (14,25,201).…”
Section: Introductionmentioning
confidence: 99%
“…The isolation of various classes of bacterial mutants unable to carry out the symbiotic process has demonstrated that a number of different steps are involved in the establishment of effective nitrogen fixation (Vincent, 1980;Beringer, 1980). However, the genetic basis of this bacterial-plant interaction is poorly understood and the characterization and manipulation of symbiotic genes has been hampered by two main problems.…”
Section: Genetic Approach To the Analysis Of Symbiosismentioning
confidence: 99%